Safety and efficacy of 3‐phytase FLF1000 as a feed additive for pigs for fattening and minor porcine species for growing. (12th August 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of 3‐phytase FLF1000 as a feed additive for pigs for fattening and minor porcine species for growing. This additive contains 3‐phytase produced by a genetically modified strain of Komagataella phaffii and it is authorised in the European Union as a feed additive for feed for chickens for fattening, laying hens, chickens reared for laying and for minor poultry species for fattening or reared for laying or for breeding. The applicant requested the extension of use of the additive to pigs for fattening and minor porcine species for growing. The FEEDAP Panel concluded that the use of the product as a feed additive for pigs raises no concerns for the consumer safety nor for the environment. The additive should be regarded as a potential respiratory sensitiser. The applicant provided a combined tolerance and efficacy trial in weaned piglets to support the safety for the target species. However, owing to the lack of precise data on the total feed intake of the animals, the FEEDAP Panel did not consider further the study for the assessment and consequently no conclusion could be drawn regarding the safety of the additive for pigs for fattening nor for other minor growing porcine species. Three studies were considered for the efficacy and from the data obtained the FEEDAP Panel concluded that the additive has the potential to be efficacious in improving the phosphorus utilisation in pigs for fattening at a minimum level of 500 FTU/kg feed. The conclusion was extrapolated to minor growing porcine species.